(untitled) - Leeson, C. Ronald (Philadenphia, 1985)
he book is written mainly for students in professional schools but it would be useful as a reference for many undergraduate courses that touch on the subject. The authors are knowledgeable in the field, having published the first nine editions of this book." "book has been useful and popular.
Keywords: Histology